Introduction. (December 2019) - Mueller, Axel
This introduction presents the articles contained in this special issue of Philosophy and Social Criticism on the topic of populism. It does so by placing them in the field of discussions that the standard conception of populism as 'illliberal democracy' has stimulated in many areas of the populism-research that was produced in response to the recent increase in populist governments in established constitutional democracies world-wide. Following the methodological canon of studies in the field, it presents the individual contributions roughly in three segments according to leading questions they focus on. In each segment, the introduction attempts to indicate the degree to which the articles depart and provide reasons for departing from the initial standard conception and thereby point to new relevant directions for further work. The first segment (articles 1. -4.) consists of essays that take on the definitional and empirical question of what and where populism is, and which varieties of it there are. The second segment (articles 5. -8.) presents new work focusing on the diagnostic question of what conditions and institutional conditions enable contemporary populism in established liberal constitutional representative democracies. They thus also aim at explaining or at least providing insight into the structures on the supply side (party politics) that make populism popular as an `outsider option'. The third and largest segment (essays 9. -15.) comprises essays that present various approaches to answering the therapeutic question what democratic political systems and societies can do to confront, absorb or internalize the lessons from populist challenges.